Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

The table describes the quadratic function [tex]$h(x)$[/tex].

\begin{tabular}{|c|l|}
\hline
[tex]$x$[/tex] & [tex]$h(x)$[/tex] \\
\hline
-3 & -2 \\
\hline
-2 & -3 \\
\hline
-1 & -2 \\
\hline
0 & 1 \\
\hline
1 & 6 \\
\hline
2 & 13 \\
\hline
3 & 22 \\
\hline
\end{tabular}

What is the equation of [tex]$h(x)$[/tex] in vertex form?

A. [tex]$h(x) = (x + 2)^2 - 3$[/tex]
B. [tex]$h(x) = (x + 1)^2 - 2$[/tex]
C. [tex]$h(x) = (x - 1)^2 + 2$[/tex]
D. [tex]$h(x) = (x - 2)^2 + 3$[/tex]


Sagot :

To solve this problem of determining the equation of \( h(x) \) in vertex form given the table of values, we'll go through a systematic approach.

First, let's recall the forms of quadratic functions:
- Standard form: \( h(x) = ax^2 + bx + c \)
- Vertex form: \( h(x) = a(x - h_v)^2 + k \), where \((h_v, k)\) is the vertex of the parabola.

Given the data points in the table:
[tex]\[ \begin{array}{|c|c|} \hline x & h(x) \\ \hline -3 & -2 \\ \hline -2 & -3 \\ \hline -1 & -2 \\ \hline 0 & 1 \\ \hline 1 & 6 \\ \hline 2 & 13 \\ \hline 3 & 22 \\ \hline \end{array} \][/tex]

1. Fit a Quadratic Function:
We fit a quadratic function \( h(x) = ax^2 + bx + c \) using the given points.

2. Determine the Coefficients:
The quadratic function that fits these points can be determined, and we find the coefficients to be \( a = 1 \), \( b = 4 \), and \( c = 1 \). Thus, the quadratic function in standard form is:
[tex]\[ h(x) = x^2 + 4x + 1 \][/tex]

3. Convert to Vertex Form:
To convert to vertex form, we use the relationship \( x = -\frac{b}{2a} \) to find the x-coordinate of the vertex. Here \( a = 1 \) and \( b = 4 \):
[tex]\[ h_v = -\frac{4}{2 \cdot 1} = -2 \][/tex]
We then find the corresponding \( y \)-value (k) by substituting \( h_v = -2 \) back into the quadratic equation:
[tex]\[ k = h(-2) = (1)(-2)^2 + 4(-2) + 1 = 4 - 8 + 1 = -3 \][/tex]

Therefore, the vertex form of the quadratic equation is:
[tex]\[ h(x) = 1(x - (-2))^2 + (-3) \][/tex]
Simplifying, we get:
[tex]\[ h(x) = (x + 2)^2 - 3 \][/tex]

4. Match with Given Options:
We compare our derived vertex form with the given options:
- \( (x+2)^2 - 3 \)
- \( (x+1)^2 - 2 \)
- \( (x-1)^2 + 2 \)
- \( (x-2)^2 + 3 \)

We see that the vertex form \( h(x) = (x + 2)^2 - 3 \) corresponds perfectly with the first option.

Thus, the correct equation in vertex form is:
[tex]\[ h(x) = (x + 2)^2 - 3 \][/tex]

Therefore, the correct choice is:
[tex]\[ \boxed{h(x) = (x + 2)^2 - 3} \][/tex]